Fraudulent Financial Statement: Pengujian Fraud Pentagon Theory Pada Sektor Industri Dan Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Cindy Syavira; Siti Aliyah (Jurnal Dinamika Ekonomi & Bisnis, 2023)
Financial Statement Fraud is fraud or manipulation of a company's financial reports to show the best condition of the company so that investors are interested and/or retain the funds they have in the company. This research is intended to analyze the influence of the factors in the fraud pentagon theory on fraudulent financial reports in manufacturing companies in the industrial and consumer goods sectors listed on the IDX in 2018-2020. The proxy variables used in this research were Institutional Ownership, Ineffective Monitoring, Change in Auditor, Change of Director, and Frequent Number of CEO's Picture. The population used for this research was all industrial and consumer goods sector companies in 2018-2020 that published complete financial reports via the IDX or company website. By utilizing purposive sampling techniques and multiple linear regression analysis processed with SPSS version 25, the results of this research showed that Institutional Ownership, Change of Director, and Frequent Number of CEO's Picture have no effect on Financial Statement Fraud. Meanwhile, Ineffective Monitoring has a positive effect and Change in Auditor has a negative effect on Financial Statement Fraud